Genome-Wide and 16S rRNA Sequencing-Based Analysis on the Health Effects of Lacticaseibacillus paracasei XLK401 on Chicks - Xin Kang; Xin-Dong Li; Huan-Yu Zhou; Feng Wang; Lian-Bing Lin (Microorganisms, 2023)
Lacticaseibacillus paracasei, serves as a growth promoter used in the poultry industry, contributeing to broiler development. However, practical studies are needed to determine the probiotic potential and growth-promoting effects of specific L. paracasei strains. This study aims to determine whether L. paracasei XLK401 influences broiler chicken growth and the mechanisms involved. Notably, we identified several bile salt and acid tolerance-related genes (Asp23, atpD, atpA, atpH, and atpF) in L. paracasei XLK401. This bacterium demonstrates robust probiotic properties under acidic conditions (pH 2.0) and 0.3% bile salt conditions. It also contains a variety of antioxidant-related genes (trxA, trxB, and tpx), carbohydrate-related genes, gene-encoding glycosidases (e.g., GH and GT), and three clusters of genes associated with antimicrobial compounds. Supplementation with L. paracasei XLK401 significantly increased the body weight of the chicks. In addition, it significantly increased hepatic antioxidant enzyme activities (GSH-Px, SOD, and T-AOC) while significantly decreasing the levels of oxidative damage factors and inflammatory factors (MDA and IL-6), resulting in improved chick health. Improvements in body weight and health status were associated with significant increases in α-amylase activity and the remodeling of the host gut microbiota by L. paracasei XLK401. Among them, actinobacteria abundance in chicken intestines after feeding them L. paracasei XLK401 was significantly decreased, Bifidobacterium sp. abundance was also significantly decreased, and Subdoligranulum sp. abundance was significantly increased. This suggests that L. paracasei XLK401 can regulate the abundance of certain bacteria without changing the overall microbial structure. In addition, in the correlation analysis, Subdoligranulums sp. were positively correlated with SOD and negatively correlated with IL-1β and MDA. Overall, our study demonstrates that L. paracasei XLK401 effectively promotes healthy chick growth. This is made possible by the modulation of gut microbe abundance and the underlying probiotic effect of L. paracasei XLK401. Based on these findings, we postulate L. paracasei XLK401 as a potential efficient growth promoter in broiler farming.